Vanadium oxide bronzes as cathode active materials for non-lithium-based batteries. Issue 31 (10th May 2021) - Esparcia, Eugene; Joo, Jin; Lee, Jinwoo
Abstract : Lithium as critical resource prompted interest for non-lithium-based batteries. This highlight review discusses vanadium oxide bronzes as one of the material families being considered as cathode for non-lithium-based batteries. Abstract : Vanadium oxide bronzes have recently been considered battery cathode materials owing to their inherent large interlayer distance for facile intercalation processes, mixed valences that can potentially provide high capacity, and good electronic conductivity. Vanadium oxide bronzes have been tested as cathodes mostly for lithium-based batteries but relatively fewer studies have been performed for non-lithium-based batteries. In this review, we look at the recent developments and approaches made by multiple battery research groups in using vanadium oxide bronzes as cathode active materials for non-lithium-based batteries. Several aspects of various vanadium oxide bronzes were elucidated in relation to the crystal structure and their interaction with other battery components. The electrochemical performances of batteries were then compared.